Association between radiation dose to the heart and myocardial fatty acid metabolic impairment due to chemoradiation-therapy: Prospective study using I-123 BMIPP SPECT/CT. Issue 1 (April 2016) - Takanami, Kentaro; Arai, Akira; Umezawa, Rei; Takeuchi, Takashi; Kadoya, Noriyuki; Taki, Yasuyuki; Jingu, Keiichi; Takase, Kei
Abstract: Purpose: To investigate long term changes in myocardial fatty acid metabolic impairment caused by chemoradiation-therapy (CRT). Materials and methods: We investigated 12 esophageal cancer patients who underwent SPECT/CT using I-123-labeled fatty acid analog (BMIPP) at pre-CRT, pre-boost irradiation, 3-month post-CRT, and 1-year post-CRT. The myocardial uptake was measured using the defect score and the total percentage of uptake (%uptake), which were defined as the sum of the visual scores and that of %uptake in each of 17 segments in the left ventricle (LV), respectively. The correlations between radiation dose to the heart (mean dose, V20, V40, and V60 of the LV and the whole heart (WH)) and the change of myocardial BMIPP uptake from pre-CRT (Δmyocardial BMIPP uptake) were assessed. Results: At pre-boost, Δmyocardial BMIPP uptake was significantly correlated with LV-V40 and WH-V60. At 3-month post-CRT, Δmyocardial BMIPP uptake was significantly correlated with LV-V40, WH-V40, and WH-V60. However, there were no statistically significant correlations at 1-year post-CRT. Neither mean dose nor V20 of the LV/WH was significantly correlated with Δmyocardial BMIPP uptake at any time. Conclusions: In the long term after CRT, myocardial metabolism might be affected by factors other than the radiation dose to the heart.